Análise da disponibilização de entendimentos administrativos no portal eletrônico e da implementação da linguagem simples e do direito visual como formas de efetivar o direito fundamental de acesso à informação na PGE/TO - Barros, Gabriela dos Santos (Universidade Federal do Tocantins, 2023)
This Conclusive Technical Report of the Research is the final product of the research conducted by the Master student in the area of Jurisdiction Instruments, Access to Justice and Human Rights and the subarea of Management, Technology, Participation and Social Control of the Interdisciplinary Professional Master Program in Jurisdiction and Human Rights of the Federal University of Tocantins in partnership with the Tocantinense Magistracy School. The research object of this Technical Report had the general objective of analyzing the availability of administrative understandings on the website and the implementation of Simple Language and Visual Law as ways to effect the fundamental human right to access information in PGE/TO. It had three specific objectives. The first one was to map the electronic portals of the Federal, District and State Public Advocacy Organs regarding the availability of their administrative understandings, the format of this availability and the safeguard of personal data according to the Law about the information access and the General Law about personal data protection. The second specific objective was to survey how Public Attorney Organs have applied Simple Language and Visual Law techniques. The third one was to identify barriers, incentives and solutions to the greater effectiveness of the fundamental right to access information in PGE/TO. Regarding the methodology, it is a qualitative research developed by the inductive scientific method because it started from the examination of particular experiences of public organs to reach a macro view of the research object, more precisely those cited in the first specific objective and the experiences with Simple Language and Visual Law of the General Attorneys of the Ceará State and of the São Paulo State and of the General Attorney of the National Treasury in partnership with ÍRIS - Innovation and Data Laboratory of the Government of Ceará. Regarding research techniques, indirect documentation was used, through documentary and bibliographic research. In addition, semi-structured interviews were conducted with 5 (five) public servants working in the Administrative, the Special Consultancy and the Study Center Subattorneyships of PGE/TO. At the end of this conclusive technical report of the research, were presented to the PGE/TO recommendations for the implementation of the fundamental human right to access information within the Public Attorney, notably the availability to the general public on the PGE website of reference opinions and opinions in response to generic consultations, the publication of monthly bulletins with selected administrative precedents and the celebration with ÍRIS of partnership without transfer of financial resources, among other recommendations. As intermediate technical professional products, the following were developed by the Master student: Proposal to create the Technical Chamber for the application of Simple Language and Visual Law and partnership with ÍRIS; Scientific Article “Participatory democracy and Democratic and Consensual Public Administration: instruments to fulfill the UN 2030 Agenda”.